CERMINAN REALITAS SOSIAL SASTRA HISTORIS: STUDI SOSIOLOGI SASTRA ATAS NOVEL REALIS AL-FARIS AL-JAMIL KARYA ALI AHMAD BAKATSIR - Muttaki, Muttaki (Majalah Ilmiah Tabuah: Ta`limat, Budaya, Agama dan Humaniora, 2024)
The novel al-Fâris al-Jamîl was written by ‘Alî Ahmad Bâkatsîr in the 19th century. This novel contains events that correspond to historical realities. This article aims to uncover the reflection of historical realities in the novel. The study employs a descriptive-qualitative method with a library research approach. Data collection was carried out using note-taking techniques. The data was then analyzed using the dialectical method to examine the congruence between events in and outside the novel al-Fâris al-Jamîl, through the theories of Frederic Jameson and Robert Scholes. The results of the study indicate that the characters in the novel al-Fâris al-Jamîl depict historical realities following the death of the Prophet Muhammad, particularly during the Umayyad period in the mid-6th to 7th centuries. This is evidenced by the inclusion of historical figures from that period in the story, including Mu?’ab bin al-Zubair, ‘Abdullâh bin al-Zubair, and ‘Abdu al-Malik bin Marwân.